Bad monkey - Hiaasen, Carl (Alfred A. Knopf, 2013)
Andrew Yancy, late of the Miami Police, soon-to-be-late of the Key West Police, has a human arm in his freezer. There is a logical explanation for that, but not for how and why it parted from its owner. Yancy thinks the boating-accident/shark-luncheon explanation is full of holes, and if he can prove murder, his commander might relieve him of Health Inspector duties, aka Roach Patrol. But first Yancy will negotiate an ever-surprising course of events, from the Keys to Miami to a Bahamian out island, with a crew of equally ever-surprising characters, including: the twitchy widow of the frozen arm; an avariciously idiotic real estate developer; a voodoo witch whose lovers are blinded-unto-death by her particularly peculiar charms; Yancy's new love, a kinky medical examiner; and the eponymous Bad Monkey.